Targeting the Immune Microenvironment in the Treatment of Head and Neck Squamous Cell Carcinoma - Wang, Hui-Ching; Chan, Leong-Perng; Cho, Shih-Feng (Frontiers in Oncology, 2019)
Head and neck squamous cell carcinoma (HNSCC) is a highly aggressive solid tumor, with a five-year mortality rate of approximately 50%. The development of immunotherapies has improved the survival of patients with HNSCC, but, the long-term prognosis of patients with recurrent or metastatic HNSCC remains poor. HNSCC is characterized by intratumoral infiltration of regulatory T cells, dysfunctional natural killer cells, an elevated Treg/CD8+ T cell ratio, and increased programmed cell death ligand 1 protein on tumor cells. This leads to an immunocompromised niche in favor of the proliferation and treatment resistance of cancer cells. To achieve an improved treatment response, several potential combination strategies, such as increasing the neoantigens for antigen presentation and therapeutic agents targeting components of the tumor microenvironment, have been explored and have shown promising results in preclinical studies. In addition, large-scale bioinformatic studies have also identified possible predictive biomarkers of HNSCC. As immunotherapy has shown survival benefits in recent HNSCC clinical trials, a comprehensive investigation of immune cells and immune-related factors/cytokines and the immune profiling of tumor cells during the development of HNSCC may provide more insights into the complex immune microenvironment and thus, facilitate the development of novel immunotherapeutic agents.